Quantifying the global 'CMB tension' between the Atacama Cosmology Telescope and the Planck satellite in extended models of cosmology. Issue 1 (14th January 2023) - Di Valentino, Eleonora; Giarè, William; Melchiorri, Alessandro; Silk, Joseph
ABSTRACT: We study the global agreement between the most recent observations of the cosmic microwave background (CMB) temperature and polarization anisotropies angular power spectra released by the Atacama Cosmology Telescope and the Planck satellite in various cosmological models that differ by the inclusion of different combinations of additional parameters. By using the Suspiciousness statistic, we show that the global 'CMB tension' between the two experiments, quantified at the Gaussian equivalent level of $\sim 2.5\, σ$ within the baseline Lambda cold dark matter, is reduced at the level of 1.8σ when the effective number of relativistic particles ( N eff ) is significantly less than the standard value, while it ranges between $2.3\, σ$ and $3.5\, σ$ in all the other extended models.